Linguistic landscapes in a Western Ukranian town - Hires-László Kornélia; Гіреш-Ласлов Корнелія (My University, 2019)
Abstract. In this paper I describe how we identified the language symbols used on street and road signs in Ukraine’s westernmost town, Berehove. In linguistic landscape studies, multiethnicity is a significant aspect indeed. Insofar as numerous ethnic groups live in Berehove side by side, it seems plausible to analyze the linguistic landscape of this settlement. In this study, two analyses (involving linguistic landscape items collected in 2013 and 2017) are used to elucidate this settlement’s linguistic landscape. I demonstrate the linguistic landscape collections using two methods of analysis (quantitative and qualitative), studied in a town characterized by its multilingual history. I also analyze ethnolinguistic vitality research in bilingual settings of various time lines. Furthermore, I introduce inscriptions and symbols collected at a street fair in relation to their language and its richness.
Editorial Board: https://cjssp.uni-corvinus.hu/index.php/cjssp/issue/view/29 Contents: https://cjssp.uni-corvinus.hu/index.php/cjssp/issue/view/29/showToc
Keywords: Transcarpathia; Berehove; linguistic landscape; multiethnicity